2013
DOI: 10.1089/ten.tea.2012.0519
|View full text |Cite
|
Sign up to set email alerts
|

BMP2-Induced Inflammation Can Be Suppressed by the Osteoinductive Growth Factor NELL-1

Abstract: Bone-morphogenetic protein 2 (BMP2) is currently the only Food and Drug Administration-approved osteoinductive growth factor used in clinical settings for bone regeneration and repair. However, the use of BMP2 is encumbered by numerous clinical complications, including postoperative inflammation and life-threatening cervical swelling. Thus, methods to prevent BMP2-induced inflammation would have far-reaching clinical implications toward improving current BMP2-based methods for bone regeneration. For the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 64 publications
0
69
0
Order By: Relevance
“…37,77 Finally, using a femoral onlay model, 12 we found that NELL-1 does not mediate inflammatory cell infiltration, in contrast to BMP2. 78 Based on these observations, we believe that NELL-1 is not directly chemotactic, but instead promotes a more directed lineage specification of BMP2-induced or recruited progenitors toward osteogenesis, while at the same time inhibiting adipogenic lineage commitment. Indeed, we observed reduced cellularity (Supplemental Figure S3) and adipogenesis (Figures 2 and 3) with NELL-1þBMP2 cotreatment compared with BMP2 treatment alone.…”
Section: Cellular Effects Of Nell-1 and Bmp2 In Femoral Segmental Defmentioning
confidence: 78%
“…37,77 Finally, using a femoral onlay model, 12 we found that NELL-1 does not mediate inflammatory cell infiltration, in contrast to BMP2. 78 Based on these observations, we believe that NELL-1 is not directly chemotactic, but instead promotes a more directed lineage specification of BMP2-induced or recruited progenitors toward osteogenesis, while at the same time inhibiting adipogenic lineage commitment. Indeed, we observed reduced cellularity (Supplemental Figure S3) and adipogenesis (Figures 2 and 3) with NELL-1þBMP2 cotreatment compared with BMP2 treatment alone.…”
Section: Cellular Effects Of Nell-1 and Bmp2 In Femoral Segmental Defmentioning
confidence: 78%
“…There are several advantages to using NELL-1 in osteoporotic conditions over BMP-2: (1) NELL-1 inhibits BMP-2 induced inflammation by acting as an anti-inflammatory molecule [7]. (2) NELL-1 has anti-osteoclastic effects [25].…”
Section: Discussionmentioning
confidence: 99%
“…For in vivo usage, superphysiological doses of the growth factors are usually needed in order to induce bone regeneration efficiently. For example, overdose of BMP2 could simultaneously cause potential side effects, such as inflammation, ectopic bone formation, and low quality of regenerated bone tissue with fatty marrow formed inside [11,12,15,55,56]. Therefore, it was necessary to find novel osteogenic growth factors for bone regeneration.…”
Section: Discussionmentioning
confidence: 99%